The Effect Of Work Planning And Work Load On Teachers 'Productivity Of Kantor Camat Kecamatan Talang Padang Kabupaten Empat Lawang - Pera Oktalia; Iskandar Iskandar; Hayani Hayani (Jurnal Fokus Manajemen, 2026)
The purpose of this study is to determine the effect of work planning and workload either partially or simultaneously on the work productivity of teachers at Karyawan Pada Kantor Camat Kecamatan Talang Padang Kabupaten Empat Lawang. The sample in this study, namely all teachers of, totaling 42 people will be sampled in this study. So the method used in this research is the census method, namely the collection of data on the entire population, or this research is also called population research. The method of analysis in this study is to use quantitative analysis using the SPSS program. Testing the effect of Work Planning (X1) on Work Productivity (Y), with partial testing obtained a significant value of 0.013 <0.05, thus Work Planning (X1) has a significant effect on Work Productivity (Y), then Ho is rejected and Ha is accepted, So the hypothesis in this study is proven to show that there is a significant influence on the Work Planning variable (X1) on Work Productivity (Y). Testing the effect of Workload (X2) on Work Productivity (Y), with partial testing obtained a Significant value of 0.009 <0.05, thus Workload (X2) has a significant effect on Work Productivity (Y), so Ho is rejected and Ha is accepted, So the hypothesis in this study is proven to show that there is a significant influence on the Workload variable (X2) on Work Productivity (Y). Simultaneous testing obtained a Sig value of 0.001 <0.05, so Ho is rejected and Ha is accepted, meaning that the Work Planning (X1) and Workload (X2) variables have a significant effect on Work Productivity (Y) together this is proven to show a significant effect.